Sustainable Islamic Education: Literature Study Towards Achieving the Vision of Sustainable Development Goals (SDGs) - Khoiriyah, Siti; Asror, Moh; Ruzakki, Hasan; Masdar Hilmy (Program Pascasarjana Universitas Ibrahimy, 2023)
Abstract: Sustainable Islamic education has an important urgency in realizing the vision of the Sustainable Development Goals (SDGs). This study uses the Systematic Literature Review (SLR) method to explore important concepts in continuing Islamic education that are relevant to the SDGs. The results of the study show that a contextual learning approach is key in increasing students' understanding of religious values and their application in everyday life according to their social and cultural context. In addition, the use of technology in Islamic learning has a significant role in expanding access to learning resources and increasing the interactivity between teachers and students. Adequate teacher competence in the fields of science and pedagogy is also a crucial factor in producing quality Islamic education. Competent teachers are able to provide teaching that is effective, in-depth, and relevant to the needs of students. Assessments tailored to students' needs and contexts help teachers monitor student progress holistically and provide constructive feedback to improve learning. Finally, good institutional management involves clear policies, optimizing resources, and creating a conducive learning environment. Overall, sustainable Islamic education that integrates the concept of contextual, technology-based learning, adequate teacher competencies, assessments according to needs, and good institutional management plays an important role in realizing quality education in accordance with the vision of the SDGs.